Evaluation of the Rapid Mastitis Test for identification of Staphylococcus aureus and Streptococcus agalactiae isolated from bovine mammary glands. - Watts, J L (1988)
A latex agglutination test system (Rapid Mastitis Test [RMT]; Immucell, Portland, Maine) containing reagents for the identification of Staphylococcus aureus and Streptococcus agalactiae from bovine intramammary infections was evaluated with 527 staphylococcal and 267 streptococcal isolates. The RMT Staphylococcus aureus reagent detected 94.2% of 242 Staphylococcus aureus isolates, 80% of 25 Staphylococcus intermedius isolates, and 42.8% of 21 tube coagulase-positive Staphylococcus hyicus isolates. All Streptococcus agalactiae isolates were correctly identified by the RMT Streptococcus agalactiae reagent. Cross-reactions were observed with one Streptococcus dysgalactiae and three Streptococcus uberis strains. The RMT was found to be an acceptable method for the detection of Staphylococcus aureus and Streptococcus agalactiae isolated from bovine mammary glands. The occurrence of coagulase-positive staphylococci other than Staphylococcus aureus requires biochemical testing for species level identification.